Hemodialysis in the Poisoned Patient - Megan Boysen-Osborn; Jeffrey R Suchard (eScholarship Publishing, University of California, 2017)
Audience: This classic team based learning (cTBL) didactic is aimed for emergency medicine residents and fourth year medical students entering emergency medicine. Introduction: Over one million visits per year to United States (US) emergency departments (ED) are related to poisonings.1 Extracorporeal treatment (ECTR), specifically hemodialysis (HD), is one potential method to enhance elimination of certain drugs and their toxic metabolites.2-12 While HD may be life-saving in certain poisonings, it may have no effect on others and it carries associated risks and costs. It is essential that emergency physicians know the indications for HD in the poisoned patient. This cTBL reviews many poisonings which may be managed by HD. Objectives: By the end of this cTBL, the learner will: 1) recognize laboratory abnormalities related to toxic alcohol ingestion; 2) calculate an anion gap and osmolal gap; 3) know the characteristics of drugs that are good candidates for HD; 4) discuss the management of patients with toxic alcohol ingestions; 5) discuss the management of patients with salicylate overdose; 6) know the indications for HD in patients with overdoses of antiepileptic drugs; 7) discuss the management of patients with lithium toxicity. Method: This didactic session is a cTBL (classic team based learning).